Effect of source and irradiation of spray-dried animal plasma on nursery pig performance in a commercial facility - DeRouchey, Joel M.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Weanling pigs (1,008; initially 13.5 lb and 18 ± 2 d of age) were used in a 13-d growth assay to determine the effects of irradiation of two different plasma sources on growth performance. From d 0 to 5 postweaning, pigs fed DuCoa® plasma had improved ADG and F/G compared to pigs fed AP 920 (American Proteins, Inc.). However, from d 5 to 13, pigs fed AP 920 had improved ADG and F/G compared to pigs fed DuCoa plasma. Overall, no differences in ADG, ADFI, or F/G were detected. In addition, no differences in ADG, ADFI, or F/G were detected between irradiated plasma compared its regular form. For the entire experiment, all pigs performed similarly, regardless of plasma source and whether the plasma was irradiated or not.
Keywords: Swine; Nursery pig; Animal plasma; Irradiation